Does the Implementation of a Clinical Care Pathway Have an Impact on Early Intravenous Fluid Therapy of Acute Pancreatitis?: A Pilot Quality Improvement Study. Issue 2 (February 2021) - Di Mauro, Davide; Smith, Radford; Wijesurendere, Chinthaka; Hubble, Sheena; Manzelli, Antonio
Abstract : Objectives: Early intravenous fluid (IVF) resuscitation is crucial in the management of acute pancreatitis; variation in IVF prescription practice had been demonstrated. This pilot study aims to assess whether the implementation of an Acute Pancreatitis Care Pathway (APCP) produces a change toward a more adequate IVF regimen in the first 24 hours. Methods: Patients with confirmed diagnosis of acute pancreatitis, from July 2015 to February 2016 (group 1) and from September 2017 to March 2018 (group 2), were considered. The APCP was developed between March 2016 and August 2017. Median IVF rate, volume, and type infused in the first 24 hours, were compared between groups. Nonparametric data were analyzed with the Mann-Whitney U test, differences in frequencies with the McNemar test; significance was set at P < 0.05. Results: Seventy-two patients were included, 36 in each group. In the first 24 hours, the median IVF rate was 177 mL/h vs 225 mL/h ( P = 0.004); Ringer lactate infusion was 30% vs 77.8% ( P = 0.0003). The median total IVF volume did not differ between groups. Conclusions: The implementation of the APCP has the potential to lead to a successful change in early IVF resuscitation practice.